Costs, demand, and producer price changes - Claire Loupias; Patrick Sevestre (European Central Bank (ECB), 2010)
We estimate an ordered probit model in order to explain the occurrence and magnitude of producer price changes in the French manufacturing sector. We use data consisting essentially of the Banque de France monthly business surveys, pooled over the years 1998-2005. Our results show that changes in the price of intermediate inputs are the main driver of producer price changes. Firms also appear to react significantly to changes in the producer price index of their industry. Variations in labor costs as well as in the production level also appear to increase the likelihood of a price change but their influence seems to be of a lesser importance. We also show that estimating an unconstrained dynamic model allows improving the estimation results as compared to those associated with a standard state-dependent model. Finally, our results point to an asymmetry in price adjustments. When they face a change in their costs, firms adjust their prices upward more often and more rapidly than they do it downward.
Keywords: C23; C25; E31; 330; Price stickiness; frequency of price changes; price setting-behavior; survey data; ordered probit model; Preisrigidität; Erzeugerpreisindex; Vorleistungen; Arbeitskosten; Preismanagement; Industrie; Frankreich